PREPARATION AND CHARACTERIZATION OF EDIBLE OIL NANOEMULSIONS FOR ENHANCED STABILITY AND ORAL DELIVERY OF CURCUMIN - Franklyne, Jonathan Sampath; Nadarajan, Abinaya; Ebenazer, Andrew; Tiwari, Nisha; Mukherjee, Amitava; Chandrasekaran, Natrajan (International Journal of Applied Pharmaceutics, 2018)
Objective: This work aims to improve the oral bioavailability and long-term aqueous stability of curcumin using various edible oil nanoemulsions (NEs). Methods: NEs were optimized using the water titration method. Curcumin was loaded into optimized emulsions, and the physicochemical characteristics were determined. Long-term stability of curcumin in the edible oil NEs was analyzed by determining the droplet size, PDI and curcumin concentrations over 4 mo. Release of curcumin from the NEs was determined using a Franz diffusion apparatus and analysed using 5 mathematical models. Results: The absorbance of curcumin was linear over the concentration range of 1 to 10 Î¼g. ml-1. The LOD and LOQ ranged from 0.57 to 1.26Î¼g. ml-1 and 1.89 to 4.19Î¼g. ml-1 respectively. All the NEs were monodisperse and had a droplet size less than 150 nm. Long-term emulsion stability shows no change in droplet size and PI (Dunnett's multiple comparisons test with a confidence interval of 95%). Olive oil NE showed significantly low release in gastric fluid (9.28%) with a good release (92.99%) in intestinal fluid and 48% in a body fluid by 8 h. Conclusion: The work highlights the use of olive oil NEs as a delivery vehicle for curcumin with excellent release characteristics and the ability to protect curcumin in an aqueous environment.